Pelatihan Alat Penilaian Autentik Berbasis Wordwall di UPT SMP Negeri 2 Bontonompo - Nursakiah, Nursakiah; Abd. Kadir Jaelani; Ikhbariaty Kautsar Qadry; Erni Ekafitria Bahar; Sitti Rahma Tahir; St. Nur Humairah Halim; Takdirmin; Andi Quraisy; Randy Saputra Mahmud; Fathrul Arriah; Ahmad Syamsuadi; Mutmainnah (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service program aimed to improve teachers’ understanding and skills in developing authentic assessment tools based on Wordwall at UPT SMP Negeri 2 Bontonompo. The program was implemented through training and mentoring activities covering needs analysis, material presentation, hands-on practice using Wordwall, and evaluation of program outcomes. The participants consisted of 13 teachers from various subject areas. Data were collected through questionnaires, pretests, posttests, and participant satisfaction evaluations. The findings showed that the program had a positive impact on improving teachers’ competence. This was indicated by the increase in the mean pretest score from 14.08 to 20.23 in the posttest. The result of the paired samples test showed a significance value of 0.000, indicating a significant difference between participants’ abilities before and after the training. In addition, the satisfaction evaluation revealed that participants responded very positively to the usefulness, method, and overall implementation of the program. The training not only helped teachers understand the concept of authentic assessment, but also encouraged them to use Wordwall as a more interactive, engaging, and relevant evaluation medium in classroom learning. Therefore, this community service program can serve as an alternative model for strengthening teachers’ competence in developing digital assessment practices in schools.